Study on the subsurface damage mechanism of optical quartz glass during single grain scratching. Issue 6 (15th March 2021) - Li, Ming; Guo, Xiaoguang; Zhai, Ruifeng; Luo, Xichun; Kang, Renke; Jin, Zhuji; Guo, Dongming
Abstract: The single grain scratching SPH simulation model was established to study the subsurface damage of optical quartz glass. Based on the analysis of the stress, strain and scratching force during scratching, the generation and propagation of subsurface cracks were studied by combining with the scratch elastic stress field model. The simulation results show that the cracks generate firstly at the elastic-plastic deformation boundary in front of the grain ( φ  = 28°) due to the influence of the maximum principal tensile stress. During the scratching process, the median crack closes to form the subsurface damage by extending downward, the lateral crack promotes the brittle removal of the material by extending upward to the free surface, and microcracks remain in the elastic-plastic boundary at the bottom of the scratch after scratching. The depth of subsurface crack and plastic deformation increases with rising scratching depth. The increase of scratching speed leads to the greater dynamic fracture toughness, accompanied by a significant decrease of the maximum depth of subsurface crack and the number of subsurface cracks. The subsurface residual stress is concentrated at the bottom of the scratch, and the residual stress on both sides of the scratch surface would generate and propogate the Hertz crack. When the scratching depth is less than 1.5 μm or the scratching speed is greater than 75 m/s, the residual stress value and the depth of residual stress are relatively small. Finally, the scratching experiment was carried out. The simulation analysis is verified to be correct, as the generation and propagation of the cracks in the scratching experiment are consistent with the simulation analysis and the experimental scratching force indicates the same variation tendency with the simulation scratching force. The research results in this paper could help to restrain the subsurface damage in grinding process.